1976
DOI: 10.2307/3279145
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Oocysts of the Bovine Coccidia Eimeria bukidnonensis Tubangui 1931 and E. wyomingensis Huizinga and Winger 1942

Abstract: Oocysts of Eimeria bukidnonenisis and E. wyomingensis were found to be morphologically similar, and could be reliably differentiated only by measurements. Pyriform oocysts of E. bukidnonensis measured 43 to 51 by 30 to 35 mum (mean 47.4 by 33.0 mum); sporocysts were 18 to 21 by 9 to 11 mum (mean 19.6 by 9.8 mum). Micropyle present; polar granule, oocyst residuum, and sporocyst residuum absent. Oocyst wall of 2 layers, 3.5 mum thick, and dark brown. Pyriform oocysts of E. wyomingensis measured 36 to 44 by 26 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…They found that 55.8% of animals up to 18 months of age and only 30.8% of those over 31 months of age were positive. These data support the hypothesis that young animals have more susceptible to infection by this parasite (COURTNEY; ERNST; BENZ, 1976). Some studies have reported the presence of Eimeria oocysts in 70% (MATJILA; PENZHORN, 2002) and 100% of samples from young animals (SAMSON-HIMMELSTJERNA et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They found that 55.8% of animals up to 18 months of age and only 30.8% of those over 31 months of age were positive. These data support the hypothesis that young animals have more susceptible to infection by this parasite (COURTNEY; ERNST; BENZ, 1976). Some studies have reported the presence of Eimeria oocysts in 70% (MATJILA; PENZHORN, 2002) and 100% of samples from young animals (SAMSON-HIMMELSTJERNA et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…Adult animals are usually asymptomatic carriers that often serve as a source of infection for juvenile animals, which are more susceptible to parasitosis (COURTNEY; ERNST; BENZ, 1976;CHIBUNDA et al, 1997;MATJILA;PENZHORN, 2002;NAJDROWSKI, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…M is present (about 3–5 in diameter) and PG, OR, and SR are absent. Oocyst wall of 2 layers, 3.5 thick, and dark brown [ 35 ]. In phylogenetic relationships of two species, the pairwise genetic distance of E. davidianusi and E. bukidnonensis at the 18S rRNA, ITS-1 and COI locus is 97.69, 97.50 and 90.29%, respectively, and phylogenetic analysis revealed that E. davidianusi was closely to E. bukidnonensis .…”
Section: Discussionmentioning
confidence: 99%
“…Where no sporocysts could be manipulated into lateral position within the oocyst, sporocyst length measurement was not taken. The oocysts were compared with some published coccidia of Artiodactyla to observe the morphological similarities and differences [ 24 , 35 , 37 – 42 ].…”
Section: Methodsmentioning
confidence: 99%